RETRACTED: Using machine learning algorithms to solve data classification problems using multi-attribute dataset - Borodulin Aleksey; Gladkov Alexey; Gantimurov Andrei; Kukartsev Vladislav; Evsyukov Dmitriy (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001